Today's business communication : a how-to guide for the modern professional - Snyder, Jason L.; Forbus, Robert (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
This handy guide to excellent business communications is perfect for both college students and business professionals. Whether preparing for a career, launching a career, or advancing in a career, the savvy professional understands that every organization expects employees to be exceptional business communicators. Today's Business Communication: A How-to Guide for the Modern Professional leads readers through the most frequently encountered business communication situations. Two business partners who are also business school professors share their combined 30 years of marketing and communication experience with readers in this accessible, entertaining, and informative guide. The authors enhance the readers' experience through anecdotes from business professionals from different industries.
1. Why must I read this book and follow your advice (or else)? -- 2. Why must I remember that nothing on the Internet ever goes away completely? -- 3. Why must I put my audience first? -- 4. Why must I remember that communication is about relationships? -- 5. Why must I master report writing? -- 6. Why must I remember the four "f" words? -- 7. Why must I give a memorable presentation? -- 8. Why must I know how to influence and persuade others? -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 119-123) and index.
Title from PDF title page (viewed on January 25, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business communication; business communication; managerial communication; communication; business writing; business reports; business letters; public speaking; presentations; Electronic books